resolva essa equação exponencial
![{2}^{3x + 1} = {4}^{x - 2} {2}^{3x + 1} = {4}^{x - 2}](https://tex.z-dn.net/?f=+%7B2%7D%5E%7B3x+%2B+1%7D++%3D++%7B4%7D%5E%7Bx+-+2%7D+)
Soluções para a tarefa
Respondido por
1
Resposta:
x=-5
Explicação passo-a-passo:
2^(3x+1)=4^(x-2)
2^(3x+1)=2^(2x-4) (bases iguais)
(3x+1)=(2x-4)
3x+1=2x-4
3x-2x=-4-1
x=-5
Usuário anônimo:
Valeu pela MR..
Respondido por
1
2^(3x+1) = (2^2)^(x-2)
3x+1 = 2.(x-2)
3x +1 = 2x - 4
3x -2x = -4 -1
x = -5
Perguntas interessantes
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Matemática,
10 meses atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Ed. Técnica,
1 ano atrás